The Implication of Oxidative Stress and AMPK-Nrf2 Antioxidative Signaling in Pneumonia Pathogenesis - Xu, Weitong; Zhao, Tingting; Xiao, Hengyi (Frontiers in Endocrinology, 2020)
Current research shows the factors such as industrial emissions, automobile exhaust and smoking can induce oxidative stress toward lung parenchyma, which often brings pulmonary diseases, for example, chronic lung obstruction diseases (COPD), asthma and pneumonia. In addition, metabolic disorders connected with energy overtake and physical inactivity can work up metabolic diseases such as diabetes and obesity. These pathologic statuses show a common phenotype in many cases, that is the accumulation of reactive oxygen species (ROS) in pulmonary tissue accompanying with activated pro-inflammatory signals and increased susceptibility of pulmonary infection. Therefore, suppressing the oxidative stress is considered as a key strategy for preventing or ameliorating the pathogenesis of pulmonary sickness. Hopefully, studies have suggested that the activation of Adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK) can effectively improve the anti-oxidative capacity of the body by repressing the inflammatory response and restoring the metabolic homeostasis in body as well as locally in lungs. One of the mechanisms which we like to emphasize in this review is about AMPK- associated nuclear factor erythroid-2-related factor 2 (Nrf2) signaling, an important cellular antioxidant pathway. We will firstly highlight the information about oxidative stress and lesions occurred in lungs and its correlation with metabolic disorder, then focus on the molecular mechanism upon AMPK-Nrf2 antioxidant pathway particularly under the situation of pneumonia triggered by oxidative stress.